Effects and risks of unconventional monetary policy - Stefan Homburg (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2017)
During and after the Great Recession, the European Central Bank adopted unconventional monetary policies that are more or less uncontroversial in the literature. By contrast, its quantitative easing (QE) program that started in 2015 is highly disputed. The article evaluates the pros and cons of such a policy.
Keywords: E51; E52; E58; 330; Quantitative easing; European Central Bank; excess reserves; money multiplier